What Enables Novel Thoughts? The Temporal Structure of Associations and Its Relationship to Divergent Thinking - Wang, Peng; Wijnants, Maarten L.; Ritter, Simone M. (Frontiers in Psychology, 2018)
The aim of the current project is to enhance our understanding of cognitive creativity, specifically divergent thinking, by employing an interdisciplinary methodological approach. By integrating methodology from computational linguistics and complex systems into creativity research, the current study aims to shed light on the relationship between divergent thinking and the temporal structure of semantic associations. In complex systems, temporal structures can be described on a continuum from (i) random to (ii) flexible-stable and to (iii) persistent. Random structures are highly unpredictable, persistent structures are highly predictable, and flexible-stable structures are in-between, they are partly predictable from previous observations. Temporal structures of associations that are random (e.g., dog - graveyard - north pole) or persistent (e.g., dog - cat - rat) are hypothesized to be detrimental to divergent thinking. However, a flexible-stable structure (e.g. dog - police - drugs) is hypothesized to be related to enhanced divergent thinking (inverted-U). This notion was tested (N = 59) in a novel association chain task, combined with a frequently used measure of divergent thinking (i.e., Alternative Uses Test). Latent Semantic Analysis from computational linguistics was used to quantify the associations, and methods from complex systems in form of Power Spectral Density analysis and detrended fluctuation analysis were used to estimate the temporal structure of those associations. Although the current study does not confirm that a flexible-stable (vs. random/persistent) temporal structure of associations is related to enhanced divergent thinking skills, it hopefully challenges fellow researchers to refine the recent methodological developments for assessing the (temporal) structure of associations. Moreover, the current cross-fertilization of methodological approaches may inspire creativity researchers to take advantage of other fields' ideas and methods. To derive at a theoretically sound cognitive theory of creativity, it is important to integrate research ideas and empirical methods from a variety of disciplines.